HMGB1 mediates splenomegaly and expansion of splenic CD11b+ Ly‐6Chigh inflammatory monocytes in murine sepsis survivors. (12th August 2013) - Valdés‐Ferrer, S. I.; Rosas‐Ballina, M.; Olofsson, P. S.; Lu, B.; Dancho, M. E.; Ochani, M.; Li, J. H.; Scheinerman, J. A.; Katz, D. A.; Levine, Y. A.; Hudson, L. K.; Yang, H.; et al.
Abstract: Background: More than 500, 000 hospitalized patients survive severe sepsis annually in the USA. Recent epidemiological evidence, however, demonstrated that these survivors have significant morbidity and mortality, with 3‐year fatality rates higher than 70%. To investigate the mechanisms underlying persistent functional impairment in sepsis survivors, here we developed a model to study severe sepsis survivors following cecal ligation and puncture (CLP). Methods: Sepsis was induced in mice by CLP and survivors were followed for twelve weeks. Spleen and blood were collected and analyzed at different time points post‐sepsis. Results: We observed that sepsis survivors developed significant splenomegaly. Analysis of the splenic cellular compartments revealed a major expansion of the inflammatory CD11b+ Ly‐6CHigh pool. Serum high‐mobility group box 1 (HMGB1) levels in the sepsis surviving mice were significantly elevated for 4‐6 weeks after post‐sepsis, and administration of an anti‐HMGB1 monoclonal antibody significantly attenuated splenomegaly as well as splenocyte priming. Administration of recombinant HMGB1 to naive mice induced similar splenomegaly, leukocytosis and splenocyte priming as observed in sepsis survivors. Interestingly analysis of circulating HMGB1 from sepsis survivors by mass spectroscopy demonstrated a stepwise increase of reduced form of HMGB1 (with known chemo‐attractant properties) during the first 3 weeks, followed by disulphide form (with known inflammatory properties) 4‐8 weeks after CLP. Discussion: Our results indicate that prolonged elevation of HMGB1 is a necessary and sufficient mediator of splenomegaly and splenocyte expansion, as well as splenocyte inflammatory priming in murine severe sepsis survivors.